De l’usage de la « crise » dans les essais de vulgarisation d’histoire économique au Chili (1860-1960) - Stéphane Boisard (Les Cahiers ALHIM)
From Jean Gustave Courcelle Seneuil’s Tratado teórico y práctico de economía política published in Chile in 1859 to the Chicago Boys’ Ladrillo, which inspired the military putschits of 1973, the « laissez-faire, laissez-passer » economic doctrine seems to have been the panacea of all the problems of the chilean economy. Nevertheless, in between these two essays, most of the intellectuals who worked on the chilean economic history criticized this theory. Whatever their ideological families, they all offered a negative interpretation of the developpement of the nation, going from « inferiority » (F. Encina) or « failure » (A. Pinto) to « eternal » (C. Keller) or « integral » (J. Ahumada) crisis. This article explores the social representations system that sustains some of the economic popularizing work from the catholic conservative thought at the end of the XIXe century to nationalist essays of the intelectual generation of the Century, ending by the structuralist theories of the 1960’s.